Open Parliament and the Modernisation of the Indonesian House of Representatives: A Qualitative Policy Analysis of Transparency, Participation, and Accountability Reforms - Azlan Dwi Rahman; Izzatussolekha Izzatussolekha (SWATANTRA, 2025)
Parliamentary modernisation has become a critical agenda in democratic governance, particularly in contexts where public confidence in representative institutions remains fragile. This study examines how the implementation of Open Parliament contributes to the modernisation of the House of Representatives of the Republic of Indonesia (DPR RI). Using a qualitative descriptive design based on documentary analysis and literature review, the study analyses official parliamentary documents, Open Parliament Indonesia materials, digital platforms, and relevant academic sources. The analysis applies two interconnected frameworks: the principles of open parliament, including transparency, participation, accountability, accessibility, and digital communication; and the criteria of a modern democratic parliament, namely representativeness, transparency, accessibility, accountability, and effectiveness. The findings indicate that Open Parliament Indonesia has strengthened the DPR RI’s modernisation agenda through several institutional innovations, including the Public Information and Documentation Officer platform, the Legislative Information System, participatory mechanisms for law-making, the redesign of the parliamentary website, and the use of parliamentary media and social media channels. These initiatives have expanded public access to legislative information and created new opportunities for civic engagement. However, several limitations remain, particularly incomplete information disclosure, uneven data quality, limited budget transparency, weak feedback mechanisms, and low public awareness. The study argues that Open Parliament should be understood not merely as digitalisation, but as an institutional reform strategy that embeds openness, deliberation, and accountability into parliamentary practice. It contributes to scholarship on legislative reform in emerging democracies and offers practical implications for strengthening governance.